The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jbt.22613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of doxycycline administration on rat embryonic development during organogenesis

Abstract: This experiment was performed to evaluate the possible embryotoxic and teratogenic effects of doxycycline during rat development. Twenty‐one female rats were used and distributed into three groups equally (seven animals/group). The low dose group received doxycycline at a dose of 5 mg/kg bw/day orally from the 6th to 14th day of gestation. The high dose group received 10 mg/kg bw/day orally for the same period, the Control group received 1 mL distilled water orally for the same period. The dams were dissected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Intrauterine organ development is vulnerable to adverse environments such as prenatal drug use, and many different kinds of drugs have been shown to damage the development of the same organ ( Table 1 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ). The liver is the crucial organ for the metabolism of many exogenous compounds, including drugs.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
See 4 more Smart Citations
“…Intrauterine organ development is vulnerable to adverse environments such as prenatal drug use, and many different kinds of drugs have been shown to damage the development of the same organ ( Table 1 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ). The liver is the crucial organ for the metabolism of many exogenous compounds, including drugs.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…The liver is the crucial organ for the metabolism of many exogenous compounds, including drugs. Studies have confirmed that hepatic development is susceptible to many kinds of drugs, including antibiotics 9 , 10 , 11 , 12 , 13 , 14 , synthetic glucocorticoids 15 , 16 , antithyroid drugs 17 , hypoglycemic agents 18 , non-steroidal anti-inflammatory drugs (NSAIDs) 19 , antipsychotics 20 , antipyretic-analgesic drugs 21 , traditional Chinese medicine (or its ingredients) 22 , 23 , 24 , 25 , 26 , 27 and so on. Hippocampal, bone, and gonadal development are also vulnerable to a variety of drugs.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
See 3 more Smart Citations